The Role of ICT Centers in the Management of Distance Education in Palestinian Universities during Emergency Education - Wajeeh Daher; Wafaa Ashour; Rabab Hamdan (MDPI AG, 2022)
The present research intended to verify the role of ICT centers in Palestinian universities in managing the academic process in emergency education due to the pandemic. The research investigated this issue using a descriptive qualitative approach. The data collection was carried out using individual interviews during the first semester of the academic year 2020/2021. The data analysis was carried out using an inductive thematic analysis. The research participants were ten officials in the ICT centers of five universities. The main study findings show that the universities performed several actions in the context of their management of the distance learning processes. These actions targeted quality education by holding workshops for the professional development of the instructor, which resulted in being a main factor in the success of the distance learning process. In addition, the ICT centers were engaged in addressing the communication between the instructor, the student, and officials at the universities. They also addressed strengthening the infrastructure for distance learning in the universities.